Examining state-dependent effects of transcranial direct current stimulation on visual search and executive function tasks. Issue 1 (6th January 2021) - Brunyé, Tad T.; Elliott, Grace; Loverro, Kari
Abstract : Objective: The aim of this study was to evaluate whether the effects of transcranial direct current stimulation (tDCS) on cognitive performance are influenced by the state-dependency of targeted cortical regions. Methods: In a mixed within- and between-participants design, we targeted either the right parietal or left dorsolateral prefrontal cortex and measured effects on visual search versus inhibitory control (respectively). Critically, during active and sham stimulation, participants were exposed to an unrelated or task-congruent prime. Results: Analyses examined whether priming induced state-dependent changes in behavior on a subsequent visual search or inhibitory control task. Results demonstrated consistent support for the null hypothesis, with neither tDCS nor priming influencing behavioral outcomes. Conclusions: This outcome does not provide direct support for state-dependency or activity-selectivity models of tDCS effects on cognitive outcomes. We discuss the possibility that behavioral patterns supporting these mechanistic models may only be found when the priming and outcome tasks share critical neurocognitive features. Overall, we found no evidence that offline (pretask) tDCS targeting the right parietal or left dorsolateral prefrontal induces reliable changes in visual search or inhibitory control behavior, and this pattern is not modulated by state-dependency induced by priming task-related activity.